2019
DOI: 10.3390/ijms20061304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of A22 on the Conformation of Bacterial Actin MreB

Abstract: The mechanism of the antibiotic molecule A22 is yet to be clearly understood. In a previous study, we carried out molecular dynamics simulations of a monomer of the bacterial actin-like MreB in complex with different nucleotides and A22, and suggested that A22 impedes the release of Pi from the active site of MreB after the hydrolysis of ATP, resulting in filament instability. On the basis of the suggestion that Pi release occurs on a similar timescale to polymerization and that polymerization can occur in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…The same study demonstrated further that the mechanism of A22 partly involves its ability to impede the release of P i from the active site of MreB after ATP hydrolysis, leading to filament instability. A more recent similar study (Awuni and Mu, 2019) showed that A22 inhibits MreB in part by impeding an ATP-induced conformational change that it requires to polymerize into stable double protofilaments. It does appear that the mechanism of A22 is multidimensional and involves several effects on the structure and dynamics of MreB.…”
Section: Mechanism Of A22mentioning
confidence: 96%
See 2 more Smart Citations
“…The same study demonstrated further that the mechanism of A22 partly involves its ability to impede the release of P i from the active site of MreB after ATP hydrolysis, leading to filament instability. A more recent similar study (Awuni and Mu, 2019) showed that A22 inhibits MreB in part by impeding an ATP-induced conformational change that it requires to polymerize into stable double protofilaments. It does appear that the mechanism of A22 is multidimensional and involves several effects on the structure and dynamics of MreB.…”
Section: Mechanism Of A22mentioning
confidence: 96%
“…Currently, the nucleotide binding site, the A22 binding pocket, and the inter-protofilament interface of MreB have been identified as potential targets for antibiotics. The nucleotide binding site is an important target for antibiotics development because nucleotide binding plays a crucial role in the structure and dynamics of MreB (Bean and Amann, 2008;Colavin et al, 2014;Van Den Ent et al, 2014;Awuni et al, 2016;Awuni and Mu, 2019). ATP induces the polymerization of MreB into filaments required for cell wall biosynthesis (Van Den Ent et al, 2001;Popp et al, 2010;Awuni and Mu, 2019).…”
Section: Targets Of Mreb For Antibiotic Discovery and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, to investigate the SMreB sequences corresponding to the sequences conserved in walled bacteria [15,16,17,29,30], we predicted the ancestral sequences and 3D structures for SMreBs 1-5, HMreB, BMreBH, and BMreB ( Fig. 2C-E, S2, Data set 3).…”
Section: Characterization Of Smrebs Based On Amino Acid Sequencesmentioning
confidence: 99%
“…walled-bacterial MreB move toward an adjacent MreB molecule to interact with each other [16], these amino acid substitutions of SMreBs, especially SMreBs 2 and 4, may affect the flexibility and interaction strength, allowing them to show polymerization characters different to those of walled-bacterial MreBs (Fig. 2F).…”
Section: Characterization Of Smrebs Based On Amino Acid Sequencesmentioning
confidence: 99%